BmCH25H, a vertebrate interferon‐stimulated gene(ISG) homolog, inhibits BmNPV infection dependent on its hydroxylase activity in Bombyx mori. (28th September 2022) - Wu, Hongyun; Xia, Junming; Fei, Shigang; Wang, Yeyuan; Zhang, Mengmeng; Guo, Yiyao; Li, Xian; Swevers, Luc; Sun, Jingchen; Feng, Min
Abstract: Cholesterol‐25‐hydroxylase ( CH25H ) has been identified as an interferon‐stimulated gene (ISG) in mammals that exerts its antiviral effects by catalyzing the conversion of cholesterol to 25‐hydroxycholesterol (25HC). However, invertebrates lack an antiviral system homologous to vertebrate interferons (IFNs) because the genomes of invertebrates do not encode IFN‐like cytokines. Nevertheless, CH25H is present in insect genomes and it therefore deserves further study of whether and by which mechanism it could exert an antiviral effect in invertebrates. In this study, the Bombyx mori CH25H ( BmCH25H ) gene, of which the encoded protein has high homology with other lepidopteran species, was identified and located on chromosome 9. Interestingly, we found that the expression of BmCH25H was significantly upregulated in B. mori nucleopolyhedrovirus (BmNPV) ‐infected BmN cells and silkworm ( B. mori ) larvae at the early infection stage. The inhibitory effect of BmCH25H on BmNPV replication was further demonstrated to depend on its catalytic residues to convert cholesterol to 25HC. More importantly, we demonstrated that during BmNPV infection, BmCH25H expression was increased through the Janus kinase–signal transducer and activator of transcription (JAK–STAT) pathway, similar to the induction of ISGs following virus infection in vertebrates. This is the first report that CH25H has antiviral effects in insects; the study also elucidates the regulation of its expression and its mechanism of action. Abstract : When silkworms are infected with BmNPV, the JAK–STAT pathway in the host innate immune pathway becomes activated by an unknown mechanism. The transcription factor BmSTAT becomes phosphorylated (p‐BmSTAT may also form complexes with other proteins) and enters the nucleus as is observed in other organisms. Phosphorylated BmSTAT recognizes the STAT transcription factor binding sequence in the promoter of BmCH25H and initiates transcription of BmCH25H . Hydroxylase activity of BmCH25H results in the conversion of cholesterol to 25HC. Reduction in the amount of cholesterol and increase in the metabolite 25HC alters the properties of the cellular membrane such that BmNPV infection becomes inhibited.